Anesthetic Management of an Obstetric Patient with Behçet's Disease Complicated by Transverse Myelitis. (24th February 2022) - Alwatban, Sara; AlAamri, Etedal; Alraffa, Abdullah; Alkhawajah, Mona
Abstract : Transverse myelitis is an acute inflammation of the spinal cord. Its annual incidence is 1–8 per million. Behçet disease is also a rare autoimmune disease. Transverse myelitis can be a manifestation of neuro-Behçet's disease. For those two rare diseases to present in one patient sets a challenge in anesthetic management. Up to our knowledge, our approach to managing these cases has not been reported in the literature. We present the case of a 37-year-old female patient in her 34 th week of pregnancy, showing manifestations of neuro-Behçet's disease and recurrent transverse myelitis. She presented to the preanesthesia clinic on a wheelchair with worsening of baseline right lower limb weakness. The patient elected for neuroaxial anesthesia, and the procedure was conducted without complications. The patient was followed up for 6 months. The neuroaxial approach was successful. Patients with neuro-Behçet's disease and transverse myelitis can be safely managed with epidural anesthesia.